(untitled) (Scientific journal of the Fergana State University, 2023)
This article is written with the purpose of the scientific disclosure of the methods, mechanisms and laws of the sentences in Uzbek language with imperative meaning, that is, persuasion, encouragement, convincing, which dominates the content of advertising. For this purpose, methods such as description, classification, associative, component and contextual analysis, structural-functional analysis have been used. As a result, the inversion is considered to be one of the most acceptable ways to increase the methodological color of the content of the message, to change it from the declarative to the emotional state, and its place in advertising texts in the nature of the Uzbek language. That is, the issue of the word order is also explained in detail, revealing the methods, mechanisms and laws of the Uzbek expression of the meaning of imperative, persuasion, encouragement, persuasion in the Uzbek language.The end of the article is characterized by presenting the fact that due to their concise and incomplete form, the elliptical constructions expressing author’s propaganda in advertising texts attract more attention than complete, complex sentences. Cohesive means (elliptical syntax, syntactic parallelism, lexical-grammatical repetitions) reduce the effectiveness of the semantic lacuna by restoring the transaction. It concludes that those means has the illocutive power of focusing person’s thought into a linguistic environment of another language, and also allows the recipient to achieve the effect of "partnering" in the interpretation of the text..